The value of liver resection for focal nodular hyperplasia: resection yes or no?. Issue 1 (December 2015) - Hau, Hans; Atanasov, Georgi; Tautenhahn, Hans-Michael; Ascherl, Rudolf; Wiltberger, Georg; Schoenberg, Markus; Morgül, Mehmet; Uhlmann, Dirk; Moche, Michael; Fuchs, Jochen; Schmelzle, Moritz; Bartels, Michael
Abstract Background Focal nodular hyperplasia (FNH) are benign lesions in the liver. Although liver resection is generally not indicated in these patients, rare indications for surgical approaches indeed exist. We here report on our single-center experience with patients undergoing liver resection for FNH, focussing on preoperative diagnostic algorithms and quality of life (QoL) after surgery. Methods Medical records of 100 consecutive patients undergoing liver resection for FNH between 1992 and 2012 were retrospectively analyzed with regard to diagnostic pathways and indications for surgery. Quality of life (QoL) before and after surgery was evaluated using validated assessment tools. Student'st test, one-way ANOVA, χ 2, and binary logistic regression analyses such as Wilcoxon–Mann–Whitney test were used, as indicated. Results A combination of at least two preoperative diagnostic imaging approaches was applied in 99 cases, of which 70 patients were subjected to further imaging or tumor biopsy. In most patients, there was more than one indication for liver resection, including tumor-associated symptoms with abdominal discomfort (n  = 46, 40.7 %), balance of risk for malignancy/history of cancer (n  = 54, 47.8 %/n  = 18; 33.3 %), tumor enlargement/jaundice of vascular and biliary structures (n  = 13, 11.5 %), such as incidental findings during elective operation (n  = 1, 0.9 %). Postoperative morbidity was 19 %, with serious complications (>grade 2, Clavien–Dindo classification) being evident in 8 %. Perioperative mortality was 0 %. Liver resection was associated with a significant overall improvement in general health (very good–excellent: preoperatively 47.4 % vs. postoperatively 68.1 %;p  = 0.015). Conclusions Liver resection remains a valuable therapeutic option in the treatment of either symptomatic FNH or if malignancy cannot finally be ruled out. If clinically indicated, liver resection for FNH represents a safe approach and may lead to significant improvements of QoL especially in symptomatic patients.